Horace Kallen confronts America : Jewish identity, science, and secularism - Kaufman, Matthew J. (Syracuse, New York : Syracuse University Press, 2019)
"During his more than fifty-year writing and teaching career, Horace M. Kallen (1882-1974), the American Jewish philosopher who coined the term "cultural pluralism," incorporated into his pragmatism-infused philosophy of life a number of different sciences, from racial science to psychology and physics. Part biography, part cultural history, "Horace Kallen Confronts America" offers fresh insight into the larger question of how social discourses shape modern American Jewish identity."--
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on October 07, 2019).
Master record variable field(s) change: 050
Keywords: Kallen, Horace Meyer, -- 1882-1974.; Kallen, Horace Meyer, -- 1882-1974.; Jewish philosophy -- 20th century; Philosophy; Jews -- Identity; Cultural pluralism; Philosophers -- United States -- Biography; United States -- Biography; BIOGRAPHY & AUTOBIOGRAPHY / Philosophers; Cultural pluralism; Jewish philosophy; Jews -- Identity; Philosophers; Philosophy; United States; 1900-1999; Electronic books; Electronic books; Biography